Atom-economic amide synthesis by using an iron-substituted polyoxometalate catalyst. Issue 8 (4th January 2022) - Wang, Aiping; Xie, Ya; Wang, Jingjing; Shi, Da; Yu, Han
Abstract : A practical strategy for amidation of various amines and carboxylic acids by using an inorganic–ligand supported iron catalyst. Abstract : We report an efficient and economical amidation strategy by using a polyoxometalate-based iron catalyst that affords the corresponding amide products in good yields. All of the aliphatic, aromatic and heterocyclic substrates are produced in high yields without additional base or organic ligands. Most importantly, the first example of heterogeneous iron(iii )-catalyzed formation of the diamides is developed.